The sasquatch escape - Selfors, Suzanne. (The imaginary veterinary ;, 2013)
Spending the summer in his grandfather's rundown town, ten-year-old Ben meets an adventurous local girl and together they learn that the town's veterinarian runs a secret hospital for imaginary creatures.